IMPLEMENTATION OF INCLUSIVE APPROACH IN EDUCATION OF LEARNERS WITH SPECIAL NEEDS IN LATVIA - Guseva, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The present article considers the provision of education for learners with special needs in modernist and postmodernist societies. It emphasizes that inclusive approach in education is a multi-stage process characterized by the following principles: provision of justice and equality, participation and inclusion, guarantee of achievement for all learners including those with special needs. The aim of the present article is to consider how keeping to the principles of inclusive approach in education initiates changes in the practical work of general education schools in Latvia and other countries having a significant experience of inclusion of learners with special needs, and how these changes lay the way to sustainable education. The article reflects the theoretical analysis of the normative documents regulating Latvian education policy and the assessment of international research results in accordance with the principles of inclusive approach and settings of sustainable education.